Eksplorasi Literasi Lingkungan Siswa Madrasah: Mengungkap Fenomena Kesenjangan antara Pemahaman Kognitif dan Habituasi Perilaku: (Exploration of Madrasah Students' Environmental Literacy: Unveiling the Gap Phenomenon between Cognitive Understanding and Behavioral Habituation) - Nurfarida, Ida Ayu; Yadi Ismail , Agus (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2026)
Environmental literacy is a crucial competence for Madrasah students, yet there is often an imbalance between theoretical understanding and practical implementation. This study aims to explore the environmental literacy profile of students at MTs Plus Ar Ruhama Caracas and unveil the relationship between cognitive knowledge and pro-environmental behavior. Methods: A descriptive quantitative approach was employed, involving 150 students (Grades VII, VIII, IX) selected through proportional stratified random sampling. Data were collected using knowledge tests and behavioral questionnaires, then analyzed using descriptive statistics and Spearman’s rho correlation. Results: The findings revealed a very high average knowledge score (85.33; SD=10.940) and a high category average behavior score (71.53; SD=9.304). Cross-level analysis showed a linear cognitive improvement trend from grade VII to IX. However, the results of the correlation test showed no significant relationship between knowledge and behavior (rs = 0.026; p = 0.756). This study uncovers an